Comparación de la composición y riqueza de especies de escarabajos coprofágos (Coleoptera: Scarabaeidae) en remanentes de bosque de la Orinoquia colombiana. - Amézquita M, Sandra J.; Forsyth, Adrian; Lopera T, Alejandro; Camacho M, Andrés (Instituto de Ecología, A.C., 1999)
A study in the Colombian Orinoquia comparing the composition and species richness of dung beetles in two types of forest remnants (a forest corridor vs three isolated patches, different in shape but similar in size), was accomplished. In total 32 species and 14 genera were captured, 30 of them were collected in the forest corridor and 29 in the patches. There was no significative difference for richness and diversity values between the two types of remnants (H'corredor=2.302, H'parches=2.531), although these values are low for the Orinoquia region. The equitability values are high for both remnants, showing a homogeneous distribution of the abundance that adjust to a lognormal curve for this dung beetle community. The similarity values are also high (Morisita-Horn = 0.877) with a 87.5% of the species shared between the two types of remnants. For this region it is possible that is more important the size than the shape of the remnant, and that the species composition of these remnants is highly similar for both of the compared areas, because these are species with wide physiological ranges tolerant to the fragmentation effects.